Corrosion resistance evaluation of acrylic coating incorporated with henna leaves extract - Mohammad Fakhratul Ridwan Zulkifli,; Mohd Sabri Mohd Ghazali,; Mohd Ikmar Nizam Mohamad Isa,; Suriani Mat Jusoh,; Yabuki, Akihiro; Wan Mohd Norsani Wan Nik, (Penerbit Universiti Kebangsaan Malaysia, 2020)
The study employs optical measurements, electrochemical studies and mechanism evaluations of an acrylic coating incorporated with henna leaves extract (HLE) at ambient temperature. The effect of concentrations variation of HLE in acrylic coating was investigated and acrylic coating with 0.2 wt/vol% (AC2) of HLE had the best performance protecting aluminium alloy 5083 from corrosion. Characterization through Fourier Transform Infrared Spectroscopy (FTIR) demonstrates the association of the carbonyl group of lawsone with the acrylic resin polymer via chain scission. A further deconvolution method was used in the range of 1550 – 1720 cm-1 and the complexation between HLE and acrylic coating was observed due to the shifting of carbonyl peak. AC2 shows the lowest water permeability value due to the compact structure and high density of the HLE colloidal system. Coating resistance shows an increasing trend upon incorporation of HLE and reaches the maximum resistance at AC2. A circuit fitting analysis of electrochemical impedance spectroscopy (EIS) indicates that all coated samples is represented by [(RfQdl)(RctQdl)(W)] circuit. Warburg impedance, W for AC2 shows the lowest value (1.21 × 10-7 Ω.s-1/2) in comparison to the other samples which indicates lower speed of diffusion. Suggested mechanism shows that HLE in AC2 was formed in a close pack structured in which providing a greater barrier effect towards corrosion susceptibility of aluminium alloy 5083.